FRI0561 Healthcare Resource Utilization and Infection Risk in Rheumatoid Arthritis Patients with and without Comorbidities. (15th July 2016) - Teeple, A.; Ryan, M.; Muirheid, L.; Ellis, L.
Abstract : Background: Rheumatoid Arthritis (RA) patients have increased risk of infection and comorbidities 1 . Understanding healthcare resource utilization (HRU) and infection risk associated with comorbidity burden in RA may facilitate awareness of outcomes and development of care coordination strategies in RA. Objectives: To estimate the differences in HRU and odds of an all-cause infection claim in RA patients with comorbidities compared to RA patients without comorbidities. Methods: RA patients identified by ICD-9 CM codes (714.xx) were identified in a transactional U.S. healthcare claims database (Symphony Health) between years 2003 to 2013. RA patients with continuous clinical activity for 1 year after the first observed RA diagnosis (index date) were included. HRU and all-cause infection claim occurrence were measured 1 year post- index. The proportion of patients with ≥1 comorbidity (Comorbidity Cohort; CC) and those without any comorbidities (No Comorbidity Cohort; NC) were summarized using descriptive statistics. The odds of developing an infection and magnitude of HRU were estimated using multivariable logistic and gamma log-link regression models, respectively. Additional independent variables used in the models included age, gender, race, region, household income, medical payer and biologic medication use. Results: 645, 158 RA patients were identified using the inclusion criteria (30% NC; 70% CC). The average age for the NC group was 56 years at RA index and 75% were female. The CC group was similar in age and gender –mean age was 58 years at RA index and 77% were female. On average, the CC group had 3 comorbidities per patient (range 1 to 18). CC patients with ≥4 comorbidities were more than 2 times as likely to have an infection claim compared to NC patients (p<.0001). Patients with ≥10 comorbidities had the highest odds ratio (OR) for an all-cause infection claim (9.81 OR p<.0001) compared to NC patients. The risk for an infection claim increases by an average of 61% for each additional comorbidity. Females were more likely to develop infection compared to males (1.41 OR p<.0001). Furthermore, the odds of an infection claim increased as comorbidity burden increased (p<.0001). Biologic use did not significantly increase the odds of an infection claim in CC patients when comorbidities were controlled for in the model (OR 1.01; p=0.1938). HRU models estimated that each additional comorbid condition was associated with approximately 43% higher total costs and 41% increase in outpatient days. Conclusions: Comorbidity burden in RA patients is associated with higher total healthcare resource and costs and higher odds of having a medical billing claim for infection. While controlling for comorbidity burden, biologic use did not significantly increase the odds of all cause infection healthcare claims. References: Gullick, N.J., Scott, D.L. co-morbidities in established rheumatoid arthritis. Best Practice & Research Clinical Rheumatology 2011; 25: 469–483 Disclosure of Interest: A. Teeple Employee of: Janssen Scientific Affairs, LLC, M. Ryan Consultant for: Janssen Scientific Affairs, LLC, L. Muirheid Consultant for: Janssen Scientific Affairs, LLC, L. Ellis Employee of: Janssen Scientific Affairs, LLC